2001
DOI: 10.1159/000054656
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Treatment That either Blocks or Augments the Estradiol-Induced Gonadotropin-Releasing Hormone Surge Is Associated with Different Patterns of Hypothalamic Neural Activation

Abstract: Progesterone can either augment or inhibit the surge of gonadotropin-releasing hormone (GnRH) that drives the preovulatory luteinizing hormone (LH) surge. This study investigated the central mechanisms through which progesterone might achieve these divergent effects by examining the effects of exogenous steroids on the activation of GnRH neurons and non-GnRH-immunopositive cells in the preoptic area/anterior hypothalamus of steroid-treated ovariectomized ewes. Fos expression (an index of cellular activation) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 54 publications
2
25
2
Order By: Relevance
“…P blocks the E 2 -induced LH surge at both the early follicular phase and the early luteal phase in rhesus monkeys with gonadal-axes intact (19). The mechanisms of action of P in its stimulatory and inhibitory effects on pituitary LH and FSH discharges are mediated by the interactions among E 2 , P, and the GnRH neurosecretory system (20,21). P administration timing was critical in determining whether it would stimulate or inhibit an ovulatory LH surge in animal studies of rhesus monkeys and ewes (20,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…P blocks the E 2 -induced LH surge at both the early follicular phase and the early luteal phase in rhesus monkeys with gonadal-axes intact (19). The mechanisms of action of P in its stimulatory and inhibitory effects on pituitary LH and FSH discharges are mediated by the interactions among E 2 , P, and the GnRH neurosecretory system (20,21). P administration timing was critical in determining whether it would stimulate or inhibit an ovulatory LH surge in animal studies of rhesus monkeys and ewes (20,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies of the effects of progesterone on estradiolinduced expression of the protein product of the immediateearly gene, c-fos, which is believed to be involved in the regulation of transcription in several neuronal systems [38], also support this idea. For example, the increase in Fos expression in GnRH and non-GnRH cells that is normally observed when a GnRH surge is induced by estradiol, is absent from rats and ewes that have been treated with progesterone to prevent activation of the surge [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of the neural mechanisms through which oestradiol acts within the hypothalamus to regulate reproduction in the ewe has led to differentiation of the GnRH/LH surge‐induction process into three stages, the absolute durations of which vary between breeds of sheep (3–6): (i) ‘activation’ (during which oestradiol concentrations must be elevated) is the stage during which oestradiol‐receptive neurones within the anteromedial hypothalamus are activated; (ii) ‘transmission’ (oestradiol‐independent) is the stage during which the activational oestradiol signal is transmitted from oestradiol‐receptive cells to GnRH‐releasing neurones; and (iii) ‘surge’ (oestradiol‐independent) is the stage during which the release of GnRH peptide into the pituitary portal vasculature increases dramatically (6, 7),…”
mentioning
confidence: 99%
“…Oestradiol positive feedback, in the ewe, can be blocked by high circulating concentrations of progesterone (11), which normally occur during the luteal phase of the oestrous cycle. Investigations of the efficacy of progesterone to block the surge, relative to the three stages of the surge‐induction process outlined above, have demonstrated that progesterone can block the surge if it is administered either coincident with (6) or immediately after (4) the stimulatory oestradiol signal (i.e. during either the activation or transmission stages of the surge‐induction process).…”
mentioning
confidence: 99%
See 1 more Smart Citation